Differential expression of host invasion-associated genes by Sarcocystis calchasi in intermediate versus definitive hosts - Kristina Maier-Sam; Oliver Rupp; Anne Voss; Saskia Nemitz; Tassilo E. Wollenweber; Tara Procida-Kowalski; Jochen Wilhelm; Achim D. Gruber; Michael Lierz (PLoS ONE, 2025)
Sarcocystis calchasi is a pathogenic apicomplexan parasite affecting avian species of several orders. To complete its heteroxenous life cycle, S. calchasi infects a wide range of avian intermediate hosts and accipitriform raptors serve as definitive hosts. The mechanism of invasion into host cells is largely understood in other apicomplexan parasites, particularly Toxoplasma gondii, which also belongs to the family of Sarcocystidae. However, Sarcocystis species exhibit several distinguishing features in their life cycles and in their secretory organelles. The composition of secretory pathogenesis determinants, including surface antigens and secretory organelle proteins, has been shown to differ between closely related species, as evidenced by Sarcocystis neurona. In this study, whole-genome sequencing was performed on S. calchasi, and transcriptomes were determined by RNA-seq of S. calchasi sporozoites and bradyzoites derived from intermediate and definitive hosts as well as from merozoites propagated in primary embryonal pigeon liver cells. The S. calchasi genome contains homologs of genes encoding proteins associated with the well-conserved host invasion machinery like AMA1 and rhoptry neck proteins, albeit with a markedly reduced number of genes encoding surface antigens, rhoptry and dense granule proteins in comparison to T. gondii. Our transcriptome analysis revealed different gene expression profiles between S. calchasi sporozoites, merozoites and bradyzoites. Factors associated with host cell attachment (surface antigens and micronemal proteins) were expressed predominantly either in sporozoites and merozoites or in bradyzoites. As sporozoites and merozoites invade various intermediate hosts and cell types whereas bradyzoites enter definitive host intestinal epithelium, their differential expression patterns indicate that S. calchasi utilizes different sets of secretory pathogenesis determinants for host cell attachment and invasion, depending on the type of host and cell.